854 Mortality Associated with Conversion of Total Hip Arthroplasty for Failed Fixation/Hemiarthroplasty for Neck of Femur Fractures. (12th October 2021) - Khan, W; Baig, A; Afzaal, Q; Davison, J; Hutchings, S; Kulkarni, A; Brown, A; Ashford, R
Abstract: Aim: To identify the mortality associated with failed internal fixation and hemiarthroplasty of neck of femur fractures. Method: Patients undergoing conversion of internal fixation / hemi arthroplasty were identified from theatre records and surgical databases. Data was stored in Microsoft Excel spreadsheet. Clinical outcomes at 30 days, 1 year and 5 years post conversion total hip replacement. Results: 60 cases were collected between June 2006 and November 2016. 46 females and 14 males involved in the case. The mean age of male patients was 66.5 and for females 67.9. 32 patients had previous sliding hip screw fixation, 12 had intra-medullary nails, 8 had cannulated screw fixation and 5 patients had hemiarthroplasty. The mean time to failure was 22 months (Range: 2 weeks to 60 months) and there were 6 cases of late posttraumatic arthritis (range 4 yrs to 23 yrs). Average time from documented failure to conversion THR was 2 months. There were 2 superficial wound infections which were successfully treated with antibiotics. There were 2 cases of deep infection which required multiple debridement, washout, and prolonged inpatient stay. Average duration of hospital stay was 5.7days. 18 patients died before 5 years for reasons unrelated to their hip. All had a functional prosthesis at time of last review. 42 patients alive at 5 years had a functional prosthesis at last review Conclusions: Total Hip Arthroplasty is a successful procedure for failed fixation / hemiarthroplasty despite the technical challenges. A 3–5-year mortality rate of 33.33 % reflects well against the NHFD 1year mortality of 30 %.